Improved Microstrip Antenna with HIS Elements and FSS Superstrate for 2.4 GHz Band Applications - Praphat Arnmanee; Chuwong Phongcharoenpanich (My University, 2018)
This research presents a microstrip antenna integrated with the high-impedance surface (HIS) elements and the modified frequency selective surface (FSS) superstrate for 2.4 GHz band applications. The electromagnetic band gap (EBG) structure was utilized in the fabrication of both the HIS and FSS structures. An FR-4 substrate with 120 mm × 120 mm × 0.8 mm in dimension ( W × L × T ) and a dielectric constant of 4.3 was used in the antenna design. In the antenna development, the HIS elemental structure was mounted onto the antenna substrate around the radiation patch to suppress the surface wave, and the modified FSS superstrate was suspended 20 mm above the radiating patch to improve the directivity. Simulations were carried out to determine the optimal dimensions of the components and the antenna prototype subsequently fabricated and tested. The simulation and measured results were agreeable. The experimental results revealed that the proposed integrated antenna (i.e., the microstrip antenna with the HIS and FSS structures) outperformed the conventional microstrip antenna with regard to reflection coefficient, the radiation pattern, gain, and radiation efficiency. Specifically, the proposed antenna could achieve the measured antenna gain of 10.14 dBi at 2.45 GHz and the reflection coefficient of less than −10 dB and was operable in the 2.39–2.51 GHz frequency range.
Keywords: Directivity; Reflection coefficient; Patch antenna; Antenna gain; Advanced Antenna and Metasurface Technologies